Assessment of psychological parameters, psychomotor speed, and quality of life in pre-hypertensive women - Prashant Keshavrao Nichat,; Neelkanth Kote,; Aalasyam Naveen,; Rahmat Abdul Rahim,; Goothy, Sai Sailesh kumar; Anita Choudhary, (Asian Journal of Medical Sciences, 2023)
Background: Individual is considered as pre-hypertensive when the blood pressure is between 120 and 139/80–89 mmHg. There is an increase in the prevalence of pre-hypertension in Indian population. Hence, early diagnosis of pre-hypertension helps to prevent these diseases and increase the quantity and quality of life. Aims and Objectives: The present study was undertaken to observe the psychological parameters, psychomotor speed, and quality of life in pre-hypertensive women. Materials and Methods: Thirty cases of pre-hypertensive women between the age of 25 and 50 years and 30 age-matched non-pre-hypertensive women were included in the study. Depression, anxiety and stress, self-esteem, negative affectivity (NA) and social inhibition (SA), and quality of life were assessed using standard questionnaires. Visual and auditory reaction time (RT) was assessed using RT apparatus. Results: There was a significant (P<0.001) lower physical health score, psychological score, social relationships score, and environmental scores pre-hypertensive women when compared to healthy individuals. There was significantly (P<0.05) longer visual and auditory RT for the right and left responses in pre-hypertensive women when compared to healthy individuals. Significantly higher (P<0.05) levels of depression, anxiety, and stress and significantly lower self-esteem scores were observed in pre-hypertensive women when compared with healthy individuals. NA and SA were significantly higher (P<0.001) in pre-hypertensive women when compared with healthy individuals. Conclusion: Pre-hypertension has strong negative impact on psychological parameters, RT and quality of life. It is the need of time to increase awareness of pre-hypertension in general population. We recommend planning and implementation of special care programs for these individuals.